Burning forests: the wood pellet industry’s framing of sustainability and its shadow places - Kinefuchi, Etsuko (Frontiers in Communication, 2024)
Woody biomass energy has exponentially grown in the last decade as a renewable energy alternative to fossil fuels. The growing trend of burning trees amid global climate crisis suggests that the wood pellet industry has been grossly successful in positioning itself as a sustainability leader. What communicative frames and strategies has the industry harnessed to communicate sustainability? What do the frames and strategies leave out? To explore those questions, this paper examines the woody biomass industry’s construction of sustainability by focusing on the case of the world’s largest wood pellet company, Enviva. Following ecolinguistics and framing theory, the first part of the paper examines the company’s website and social media presence to unpack the frames that Enviva engages to communicate its sustainability. Then, the paper turns to the spheres of life that the company omits from its framing but are crucial to the conceptualization of sustainability from an ecojustice perspective. The paper concludes with a call for ecojustice as the framework for evaluating sustainability of life on land.